-2t-1=3t-16

Simple and best practice solution for -2t-1=3t-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2t-1=3t-16 equation:


Simplifying
-2t + -1 = 3t + -16

Reorder the terms:
-1 + -2t = 3t + -16

Reorder the terms:
-1 + -2t = -16 + 3t

Solving
-1 + -2t = -16 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
-1 + -2t + -3t = -16 + 3t + -3t

Combine like terms: -2t + -3t = -5t
-1 + -5t = -16 + 3t + -3t

Combine like terms: 3t + -3t = 0
-1 + -5t = -16 + 0
-1 + -5t = -16

Add '1' to each side of the equation.
-1 + 1 + -5t = -16 + 1

Combine like terms: -1 + 1 = 0
0 + -5t = -16 + 1
-5t = -16 + 1

Combine like terms: -16 + 1 = -15
-5t = -15

Divide each side by '-5'.
t = 3

Simplifying
t = 3

See similar equations:

| 3z-13=-10 | | 4x-2y=-12 | | -2+6=4v-6v | | 42m^2-29mn-5n^2= | | 9x+-2=4x+9 | | 0=8x+39 | | Y-2.8=2.2 | | Y-2.8=2.3 | | 15+8k=-34 | | 2x+3-x=6 | | 7y^2-4y-6= | | 6x+-1=x+13 | | s+2.5=6.25 | | 6(2X-4)=-32 | | -38=5x-x+10 | | 3x+(x+2)=20 | | 10x+-1=8x+6 | | 3x+9-x+4-2x=18 | | 9-24u+16u^2= | | 5x+-1=2x+11 | | 81-18s-3s^2= | | 7(x+3)-2(3x+1)=25 | | y^2+64=0 | | 38-30v=32 | | 150-5s-5s^2= | | 12x+-4=8x+24 | | 4x+0y+2z=24.94 | | 11-6x^2-31x= | | 6x+4y+1z=36.39 | | -7+7x-x=-1 | | 13-12d^2-35d= | | 10x+-6=7x+9 |

Equations solver categories